Restorative Justice pada Kejaksaan RI Sebagai Wujud dari Tujuan Bela Negara - Adhi Prasetya Handono (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Analyze and describe restorative justice as a manifestation of the goal of defending the country at the prosecution stage at the Indonesian Attorney General's Office. This research is classified as normative legal research because it employs a statutory approach to examine the problems to be discussed using legal regulations as secondary data. The analysis was conducted qualitatively, and the problem formulation was discussed using a literature review. Settlement of criminal cases based on restorative justice at the prosecution level can not only reduce the accumulation of cases and the problem of overcrowding in detention centers / correctional institutions, but it can also improve public safety, as well as a demonstration of professional skills in the function of state service to the community as a form of national service via law enforcement and community norms, as desired by the parties (victims, perpetrators and the community). The litigants' recovery is based on Perja No. 5 of 2020 concerning the Termination of Prosecution Based on Restorative Justice. Based on these provisions, the Indonesian Attorney General's Office will hold further discussions about the settlement of criminal cases based on restorative justice during the prosecution stage.